Antecedents of Online Repurchase Intention in Indonesia - Ignatius Hari Santoso (Universitas Sebelas Maret, 2017)
Online buying activity is increased along with the increased of internet-based information technology. This gives benefit to online businessman and businesswoman. However, the efforts which should be given are harder than before because of the increasing of online criminality which happened in Indonesia. The objective of this study generally is to reveal the antecedents of online repurchase intention in Indonesia. This study is using 170 respondents who have experience in online purchasing at least one times before. Visual Partial Least Square is used to examine the relationship between constructs. This study concludes that the developed model which used in this study can be used to predict online repurchase intention even several relationships is found not significant. Another conclusion from this study is perceived information quality, perceived service quality, subjective norms, online shopper’s trust, and online shoppers’ satisfaction are the antecedents of online repurchase intention.